Diagnostic accuracy of the Tilburg Frailty Indicator (TFI) for early frailty detection in elderly people in Iran. (November 2020) - Mazoochi, Faezeh; Gobbens, Robbert J.J.; Lotfi, Mohammad-sajjad; Fadayevatan, Reza
Highlights: Frailty is a common clinical syndrome in the elderly. Screening allows early intervention in frailty. Early detection and intervention in frailty help improve the quality of life of the elderly. The TFI is a highly sensitive tool for detecting frailty. Abstract: Aim: Screening is one of the most important ways for early frailty detection that contributes to its prevention and timely treatment. The aim of this study was to determine the diagnostic value of the Persian version of the Tilburg Frailty Indicator (P-TFI) in the frailty screening. Method: This is a diagnostic test accuracy study that uses known group method. It was designed based on a STARD statement and performed on 175 elderly people in the City of Kashan, Iran. The subjects were selected among older people available in health centers affiliated to Kashan University of Medical Sciences using purposive sampling. Data analysis was carried out using SPSS v16. Descriptive statistics were used to describe the characteristics of the research subjects. Independent t -test was used to determine the ability of the P-TFI to discriminate frail and non-frail individuals, and to evaluate the cut-off point and instrument accuracy, the receiver operating characteristic (ROC) curve was used. The best cut-off point was determined among the proposed points using Youden index. At the determined cut-off point, the diagnostic value parameters of the P-TFI (sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, accuracy, and diagnostic odds ratio) were calculated and their range was estimated with 95 % confidence interval. Findings: A total of 74.3 % of the sample was male and their mean age was 68.6 ± 54.44 years. The area under the ROC curve was calculated 0.922, indicating high accuracy of the instrument. The sensitivity and specificity of this instrument at the cut-off point of 4.5 were 0.95 and 0.86, respectively. Positive and negative predictive values were calculated 0.68 and 0.98, respectively, and the accuracy of the instrument was reported to be 0.88. Conclusion: The P-TFI can be used as a sensitive and accurate instrument, which is highly applicable to screen frailty in older people.